2011
DOI: 10.1183/09031936.00187510
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled dry powder mannitol in cystic fibrosis: an efficacy and safety study

Abstract: This international phase III study of inhaled dry powder mannitol was a randomised, double-blind, 26-week study, followed by a further 26-week, open-label (OL) extension. 324 cystic fibrosis (CF) patients were randomised, in a 3:2 ratio, to mannitol (400 mg b.i.d.) and control groups. The primary efficacy end-point was to determine the change in forced expiratory volume in 1 s (FEV1) over the double-blind phase. Secondary end-points included changes in forced vital capacity and pulmonary exacerbations.A signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
1
15

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(118 citation statements)
references
References 34 publications
5
97
1
15
Order By: Relevance
“…However, in the phase 3 trial, patients ≤11years in the placebo group showed an improvement in percent-predicted FEV 1 AUC 0-4h over time, which suggests a learning effect during the trial among the younger patients, who were less skilled in performing spirometry. In a recent study of inhaled mannitol, a sustained, significant (p<0.001) improvement in FEV 1 was seen in the control group [12], but the improvement was not significant in another similarly designed study (p=0.059) in similar populations [13]. Interestingly, in the pooled analysis, significant improvements in the mannitol versus control group in FEV 1 occurred in patients aged ≥18 years old but not in younger participants [14].…”
Section: Discussionmentioning
confidence: 91%
“…However, in the phase 3 trial, patients ≤11years in the placebo group showed an improvement in percent-predicted FEV 1 AUC 0-4h over time, which suggests a learning effect during the trial among the younger patients, who were less skilled in performing spirometry. In a recent study of inhaled mannitol, a sustained, significant (p<0.001) improvement in FEV 1 was seen in the control group [12], but the improvement was not significant in another similarly designed study (p=0.059) in similar populations [13]. Interestingly, in the pooled analysis, significant improvements in the mannitol versus control group in FEV 1 occurred in patients aged ≥18 years old but not in younger participants [14].…”
Section: Discussionmentioning
confidence: 91%
“…However, the precise role played by EPS during infection of the CF lung remains unclear, and direct evidence for EPS production by BCC within the lung is currently lacking. The fact that mannitol promotes EPS biosynthesis has also gained further clinical relevance following the approval of a dry-powder preparation of mannitol for use as an inhaled osmolyte in CF patients (Jaques et al, 2008;Daviskas et al, 2010;Teper et al, 2011;Bilton et al, 2011). Since colonization with BCC was amongst the exclusion criteria for participation in the mannitol powder clinical trials, the impact of this osmolyte therapy on the course of infection in Burkholderia-infected patients has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…A CF súlyosságának megítélésére az 1958-ben publikált, még napjainkban is egyszerűen és hitelesen alkalmazható pontrendszert használtuk [19]. Az összpont-szám négy fő területből adódik: általános aktivitás, fi zikális vizsgálat, tápláltsági állapot és radiológiai lelet.…”
Section: Shwachman-kulczycki-pontszám (Sk-pontszám)unclassified